Clinical characteristics and risk factors of periprosthetic femoral fractures associated with hip arthroplasty: A retrospective study. Issue 35 (August 2016) - Zhang, Zhendong; Zhuo, Qi; Chai, Wei; Ni, Ming; Li, Heng; Chen, Jiying
Abstract : Abstract: Periprosthetic femoral fracture (PFF) is a complicated complication of both primary and revision hip arthroplasty with an increasing incidence. The present study aimed to summarize the clinical characteristics and identify the risk factors for PFF which would be potentially helpful in the prevention and treatment of PFF. We retrospectively analyzed the clinical data of 89 cases of PFF, and a case–control study was designed to identify the potential risk for intraoperative and postoperative PFF in both primary and revision hip arthroplasty. The overall incidence of PFF was 2.08% (intraoperative: 1.77%, postoperative: 0.30%, revision: 13.60%, and primary: 0.97%). The most commonly used treatment strategy was fixation with cerclage wire or band for intraoperative PFF, whereas long stem revision with plate or cortical allograft strut fixation was the main treatment strategy for postoperative PFF. The risk factors for intraoperative PFF in primary total hip arthroplasty (THA) included the diagnosis of development dysplasia of the hip (DDH) (odds ratio [OR] = 5.01, 95%CI, 1.218–20.563, P =0.03) and CBR ≥ 0.49 (OR = 3.34, 95%CI, 1.138–9.784, P  = 0.03). The increased age was associated with increased incidence of postoperative PFF in primary THA (OR = 1.09, 95%CI, 1.001–1.194, P  = 0.04). As for the intraoperative PFF in revision THA, we found that receiving multiple operations before revision (OR = 2.45, 95%CI, 1.06–5.66, P  = 0.04), revisions due to prosthetic joint infection (OR = 6.72, 95%CI, 1.007–44.832, P  = 0.04), the presence of cementless implant before revision (OR = 13.54, 95%CI, 3.103–59.08, P  = 0.001), and femoral deformity (OR = 8.03, 95%CI, 1.656–38.966, P  = 0.01) were all risk factors. Screening for high-risk patients, preoperative templating, and detailed discharge instructions may be the potential strategies to reduce the incidence of PFF. The treatment of PFFs should take into account Vancouver classification system, patient's characteristics as well as the experience of the operating surgeon.